2007
DOI: 10.1007/s00228-006-0256-2
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of urapidil and doxazosin on heart rate

Abstract: We conclude that the increase in heart rate caused by urapidil is less pronounced than that with doxazosin, a property that might favour urapidil in the treatment of arterial hypertension. In addition, only doxazosin (but not urapidil) increased the RPP at rest, a finding that might be helpful to explain why this drug was never shown to improve outcome in the treatment of arterial hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
2
0
2
Order By: Relevance
“…Unfortunately the attempt was not successful, presumably due to undesirable side effects. In a more recent human study comparing cardiovascular effects of urapidil and idazoxan (a 1 -adrenoreceptor antagonists), it has been found that both drugs produced hypotension, but only in the case of idazoxan was it associated with tachycardia (presumably baroreflex-mediated) (Stoschitzky et al, 2007). Authors suggested that 5-HT1A agonist properties of urapidil could be the explanation of its more beneficial therapeutic profile.…”
Section: Clinical Perspectives Of New Applications For 5-ht1a Agonistsmentioning
confidence: 97%
“…Unfortunately the attempt was not successful, presumably due to undesirable side effects. In a more recent human study comparing cardiovascular effects of urapidil and idazoxan (a 1 -adrenoreceptor antagonists), it has been found that both drugs produced hypotension, but only in the case of idazoxan was it associated with tachycardia (presumably baroreflex-mediated) (Stoschitzky et al, 2007). Authors suggested that 5-HT1A agonist properties of urapidil could be the explanation of its more beneficial therapeutic profile.…”
Section: Clinical Perspectives Of New Applications For 5-ht1a Agonistsmentioning
confidence: 97%
“…Так, при сопоставимом снижении АД доксазозин достоверно увеличивал ЧСС в сравнении с плацебо (∆25%; p<0,05), в то время как урапидил -нет (∆12%; p>0,05). И при сравнении групп урапидила и доксазозина выявлено, что ЧСС в группе доксазозина была достоверно выше (p<0,05) [14].…”
Section: Discussionunclassified
“…Загальновідомо, що рівень артеріального тиску і частота серцевих скорочень корелюють із серцево-судинною захворюваністю й смертністю, особливо від ішемічної хвороби серця (ІХС) і її гострих ускладнень. У зв'язку з цим особливе значення має той факт, що урапідил (Ебрантил) має менший (+12 %) вплив на частоту серцевих скорочень порівняно з доксазозином (+25 %, р < 0,05) при однаковій ефективності зниження артеріального тиску [13,21].…”
Section: вступunclassified